Modification and Performance Evaluation of a Fish Feed Pelletizing Machine - Malgwi, G. S.; Abdulkadir, S. A.; Dodo, S. M. (ARID ZONE JOURNAL OF ENGINEERING, TECHNOLOGY AND ENVIRONMENT, 2020)
A hand operated fish feed pelletizing machine for the production of fish feed with through put capacity of 2.56 kg/h was modified, fabricated and evaluated due to non-availability of electricity in the rural area, drudgery and low throughput capacity. It consists of a hopper, barrel that houses the screw conveyor (auger), the cutting knife, and the die orifice. Power supply to the machine is a 6-kw petrol engine. It was observed that the pelletizing efficiency and throughput capacity increase with proportionality of smallness of die diameter. The modified machine test results showed highest throughput capacity of 162.8 kg/h with maximum pelletizing efficiency of 85.3%. The total production capacity of the machine was 150 tons per day, which is adequately to feed up to 3,000 fish per day. The adoption of the pelletizing machine by farmers will enable them produce their own feed from local plant and animal waste source thereby alleviating the problems associated with the sourcing of imported feeds.